2013
DOI: 10.1161/atvbaha.112.300121
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Potentiates Bone Morphogenetic Protein Signaling in Pulmonary Arterial Smooth Muscle Cells and in Experimental Pulmonary Hypertension

Abstract: Key Words: BMP signaling pathway ◼ cGKI ◼ PDE5 inhibitor ◼ pulmonary hypertension ◼ smooth muscle cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…We further showed that Id1 and Id2 are involved in the inhibition of PASMC proliferation by BMP4. We have also shown that agents enhancing BMP/ Smad/Id signaling in PASMCs can restore the growth-suppressive effects of BMPs in BMPR-II mutant cells (38,39).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…We further showed that Id1 and Id2 are involved in the inhibition of PASMC proliferation by BMP4. We have also shown that agents enhancing BMP/ Smad/Id signaling in PASMCs can restore the growth-suppressive effects of BMPs in BMPR-II mutant cells (38,39).…”
mentioning
confidence: 70%
“…Samples were electrophoresed by 12% SDS-PAGE and then transferred to PVDF membrane (GE Healthcare). For studies of BMPR2, Smad1/5, Id1, and Id3, blots were incubated with polyclonal mouse anti-BMPR2 (1:1,000, BD Biosciences), polyclonal rabbit antiphospho-Smad1/5 (1:1,000, Cell Signaling Technology), polyclonal rabbit anti-Id1 (1:1,000, Biocheck), polyclonal rabbit anti-Id3 (1:1,000, CalBioreagents), as previously described (39). To confirm equal protein loading, blots were stripped and reprobed using anti-␤-actin (1:4,000, Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None activated BRE-luciferase, although iloprost can induce ID1 by a pSMAD1/5-independent, cAMP-mediated mechanism (54). Recent data suggest that other medications approved and effective for PAH, such as the vasodilator and phosphodiesterase inhibitor sildenafil, can partially restore BMPR2 defective signaling (55), underscoring the importance of this pathway in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (34) reported that sildenafil enhances standard bone morphogenetic protein signaling through c-GMP and c-GMP-dependent protein kinase I in vivo and in vitro. Yaman et al (35) reported that, in rats, sildenafil could be used as a supporting factor to accelerate the healing process of defective bone in oral and maxillofacial surgeries.…”
Section: Discussionmentioning
confidence: 99%